Structure of 413.5-m deep ice core obtained at Mizuho Station, Antarctica - Narita,Hideki; Nakawo,Masayoshi (1985)
P(論文) Ice cores down to a depth of 413.5m were obtained at Mizuho Station (70°41.9'S, 44°19.9'E), East Antarctica, in April to July, 1983. Grain features (size, periphery length and shape factor) and air bubble morphology were examined from thin section photographs taken within a month after the recovery of the ice cores. The showed discernible differences from those of the similar examinations previously done of ice cores of the same place recovered in 1972. The differences are attributed to the fact that the latter examinations were based on the photographs taken much later after the recovery. Fabric patterns were also examined at selected depths also within one month after the recovery. departmental bulletin paper